Modeling of prevalence of methods of utilization of dump gas for development of equipment and strategy of handling hard domestic wastes - Bereziuk, O. V. (Visnyk of Vinnytsia Politechnical Institute, 2014)
Parameters that influence on prevalence of methods of utilization of the obtained dump gas in different countries are de-termined. The mathematical models of prognostication of prevalence of methods of utilization of the obtained dump gas are developed in the paper.